MENINGKATKAN KEMAMPUAN BERBICARA SISWA DALAM MENCERITAKAN KEGEMARAN MELALUI TEKNIK PERCAKAPAN - Ngalimun, Ngalimun (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2016)
Their speaking ability by using conversational techniques arevery important and far-reaching. This is shown by the results of the acquisition of scores of observations made respondents, who answered